A 6 Ma record of palaeodenudation in the central Himalayas from in situ cosmogenic 10Be in the Surai section. (4th October 2020) - Charreau, Julien; Lavé, Jérôme; France‐Lanord, Christian; Puchol, Nicolas; Blard, Pierre‐Henri; Pik, Raphaël; Gajurel, Ananta Prasad; ,
Abstract: To better constrain late Neogene denudation of the Himalayas, we analysed in situ 10 Be concentrations in 17 Neogene sediment samples of the Surai section (central Nepal) and two modern sediment samples of the Rapti River. We first refined the depositional ages of the Surai section from 36 new paleomagnetic analyses, five 26 Al/ 10 Be burial ages, and, based on the Dynamic Time Warping algorithm, 10 4 automatically calculated likely magnetostratigraphic correlations. We also traced changing sediment sources using major element and Sr‐Nd isotopic data, finding at 4–3 Ma a switch from a large, trans‐Himalayan river to a river draining only the Lesser Himalaya and Siwalik piedmont, increasing the contribution of recycled sediments at that time. 10 Be concentrations in Neogene sediments range from (1.00 ± 0.36) to (5.22 ± 0.98) × 10 3 at g –1 and decrease with stratigraphic age. Based on a flood plain transport model, our refined age model, and assuming a drainage change at 4–3 Ma, we reconstructed 10 Be concentrations at the time of deposition. Assuming cosmogenic production rates similar to those of the modern basins, we calculated palaeodenudation rates of 0.9 ± 0.5 to 3.9 ± 2.7 mm a –1 from ca. 6 to 3 Ma in the palaeo‐Karnali basin and 0.6 ± 0.2 to 1.6 ± 0.8 mm a –1 since ca. 3 Ma in the palaeo‐Rapti basin. Given the uncertainties and similar modern values of 2 mm a –1, the palaeo‐Karnali denudation rates may have been steady at 1.7 ± 0.3 mm a –1 for the last ca. 6 Ma. A transient acceleration of the denudation in the palaeo‐Rapti basin of 1.5 mm a –1 since ca. 1.5 Ma was likely due to the reworking of older, 10 Be‐depleted Siwalik sediments in the foreland. If true, this steadiness of the denudation rates may suggest that Quaternary glaciations did not largely affect Himalayan denudation. Abstract : Temporal evolution of reconstructed 10Be palaeoconcentrations and derived palaeodenudation rates in the Surai Khola. Palaeoconcentrations (left) are corrected for radioactive decay and exposure in the floodplain (see text). Denudation rates were calculated assuming that the sediments of the Surai section were deposited by a Karnali‐type trans‐Himalayan river prior to ca. 3.5 Ma (middle), and by a Rapti‐type midland‐draining river since ca. 3.5 Ma (right).